Encyclopedia of goddesses and heroines - Monaghan, Patricia (Novato, California New World Library, 2014)
"Documents goddesses and mythological heroines from cultures around the world, covering Africa, the eastern Mediterranean, Asia, Europe, and the Americas, including the pantheons of the world's religious traditions. By a pioneer in women's spirituality"--Provided by publisher.
Introduction-- Note on Spelling and Pronunciation-- Africa-- Introduction-- African Pantheon-- Egyptian Pantheon-- African Diaspora Pantheon-- 'Eastern Mediterranean-- Introduction-- Eastern Mediterranean Pantheon-- Christian and Jewish Pantheon-- Asia and Oceania-- China and Korea-- Introduction-- Chinese, Mongol, and Taiwanese Pantheon-- Korean Pantheon-- Circumpolar North-- Introduction-- Circumpolar North Pantheon-- India-- Introduction-- Hindu and Buddhist Pantheon of India, Nepal, and Tibet-- Southeast Asia and Indonesia-- Southeast Asian and Indonesian Pantheon-- Japan-- Introduction-- Japanese and Ainu Pantheon-- The Pacific Islands and Australia-- Introduction-- Pacific Islands Pantheon-- Australian Pantheon-- 'Europe-- The Baltic-- Introduction-- Baltic Pantheon-- The Celtic World-- Introduction-- Continental Celtic and Breton Pantheon-- Irish and Scottish Pantheon-- British and Manx Pantheon-- Welsh, Cornish, and Arthurian Pantheon-- Finno-Ugric Cultures-- Introduction-- Finno-Ugric Pantheon-- Greece-- Introduction-- Greek Pantheon-- Rome-- Introduction-- Roman and Italic Pantheon-- Etruscan Pantheon-- Scandinavia-- Introduction-- Scandinavian Pantheon-- Southeastern Europe-- Introduction-- Southeastern European Pantheon-- Slavic Peoples-- Introduction-- Slavic Pantheon-- The Americas-- North America-- Introduction-- North American Pantheon-- Mesoamerica-- Introduction-- Mesoamerican Pantheon-- South America and the Caribbean-- Introduction-- South American and Caribbean Pantheon-- Bibliography-- Index
Includes bibliographical references and index.
Keywords: Goddesses -- Encyclopedias; Women heroes -- Encyclopedias